Onling Shopping and its implications on Increasing consumerism in the Iraq Society study in Mosul City: شش - Ameerah Waheed Katab, Assist. Prof. Dr. (lark, 2024)
The importance of the research lies in knowing the impact of electronic shopping in increasing consumerism in Iraqi society in general and the city of Mosul in particular the research objectives include: • Identify the advantages of online shopping that affect the increase in Consumerism. • Knowing the most important factors that increase consumerism. • Knowing the effect of promotional methods and advertisements in increasing consumerism. The researcher used the social survey method and used tools Represented by (questionnaire and observation from). The research sample was A random, intentional study consisting of (200) respondents in the city of Mosul. The data was processed statistically and the researcher arrived at a set of results, including: • One of the most important factors that increases consumerism is the individuals access to social status. • The delivery service contributed to online shopping and increased consumerism. • Attractive promotions and advertisements have increased shopping and consumerism. Reducing time and effort in online shopping increases consumerism.